Investigating Factors Affecting the Economic and Social Resilience of Rural Areas (Case Study, Kermanshah County) - Masood Safari Aliakbari (برنامه ریزی فضایی, 2022)
AbstractRural areas are always exposed to serious risks and damages, which shows the importance of risk management and forecasting. Resilience is an approach that can help improve rural areas and their response in the face of crisis. In this study, the aim is to identify and analyze the factors affecting the economic and social resilience of rural areas in the form of a case study in Kermanshah. The research method is descriptive-analytical and based on data collection through the field approach. The data collection tool was a questionnaire. The structural and content validity of the questionnaire was approved and its reliability was also confirmed with a Cronbach's coefficient greater than 0.74. The statistical population of the research was formed by the heads of households in the villages with more than 100 households in the central part of Kermanshah city, which were a total of 2314 households. The sample size was determined through Cochran's formula, 330 household heads. The result of the test showed that the economic and social resilience of rural areas is significant at the level of less than 0.05 and according to the calculated average (2.386), their condition is evaluated as unfavorable. Among the 11 indicators of economic and social resilience, two indicators of damage with an average of 3.962, and then preparedness to deal with accidents among villagers with an average of 3.093 had an average status and the rest of the indicators were weak. Also, the results of the factor analysis confirm that the three factors of the prosperity of economic platforms and job creation, improvement of human and social capital, as well as the creation of facilities and income capacities, are the most influential factors in the resilience of rural areas.Keywords: Economic and Social Resilience, Rural Areas, Kermanshah County. IntroductionRural areas are not exempt from natural crises and possible damages. Today, rural areas are facing many problems and dilemmas, one of these problems is natural hazards that occur suddenly in villages. How to deal with these risks has led to the discussion of resilience against risks in societies today. Resilience indicators against damages and crises are one of the basic criteria in the process of planning and evaluating adaptation programs to the effects of natural hazards in rural areas. Evaluating and measuring the resilience of rural communities is one of the most important tools in diagnosing the stability of rural settlements when risks and crises occur. Rural areas are always exposed to serious risks and damages, which shows the importance of risk management and forecasting. Resilience is an approach that can help improve rural areas and their response in the face of crisis. This research aims to identify and analyze the factors affecting the economic and social resilience of rural areas as a case study in Kermanshah County. Materials and MethodsThe research method of this quantitative and applied study is based on the descriptive-analytical approach. The research data are the result of a survey study at the level of rural areas. The main tool of the research is the researcher's questionnaire, whose validity was confirmed by experts. Its reliability was also confirmed through Cronbach's alpha coefficient, which obtained a high value of 0.74 for different parts of the questionnaire. The statistical population of this research was formed by the heads of rural areas of more than 100 households in the central part of Kermanshah. According to the last census (2015), the population of these villages was 8210 people and 2314 households. The sample size was calculated using Cochran's formula to be 330 people at the level of household heads. SPSS software and appropriate statistical tests were used for data analysis. Research FindingsThe result of the test showed that except for the variable of dependence on a job with a significance level of 0.195, other economic variables were significant at a level of less than 0.05. Examining the significance direction using the average shows that the variables of the state of the cultivated area (3.139), dependence on a job (3/078), and the status of women's participation in household employment (3/472) were at a moderate level. In addition, the variables of the amount of damage caused to capital and assets (housing, livestock, etc.) with an average of 3.942, the vulnerability of income and assets with an average of 3.981, and willingness to receive a loan with an average of 4.003 were at an acceptable level. The result shows that other variables of economic resilience, such as the importance of savings and investment, the amount of access to production factors, the amount of assets and fixed capital, the areas of employment creation, etc., were poorly evaluated.The result of the sample t-test shows that all variables of social resilience in rural areas were significant at a level less than 0.05 and equal to 0.000. Examining the significance direction indicates that only the variables belonging to the village with an average of 3.487, ethnic belonging to the village with an average of 3.672, the situation and trend of migration from the village with an average of 3.700, and the physical and mental health of the villagers with an average of 3.690 are known to be in an average state compared to other variables of social resilience. The result of the test shows that other variables of social resilience, including membership in different groups of the village, participation in the village's common benefit activities, cooperation and interaction of the villagers towards each other, the situation and structure of the village population, knowledge and awareness of dealing with crisis, skills and the ability to deal with the crisis, and the existence of associations (communities) were at a weak and inappropriate level.The result of the test in the field of 6 indicators of economic resilience and 5 indicators of social resilience shows that all resilience indicators were significant at the level of less than 0.05. Examining the significance direction indicates that the average of all economic and social resilience indicators, except for the two indicators of damage and preparedness to deal with accidents, is lower than the average of the test (3), and therefore the resilience situation in rural areas is evaluated as weak. Examining the total resilience in rural areas also confirms this point because the result of the test shows that the level of resilience in rural areas is less than 0.05 and the average is 2.386.Also, the results showed that rural areas (20 villages) in terms of damage indicators, disaster preparedness among villagers, economic capital and assets, employment, cost and income, benefit from banking resources, capacity to return to employment and income conditions, social belonging, social participation, resources and human capital, and the capacity of spontaneous and people's institutions have no significant difference. Discussion of Results and ConclusionThe result of the study showed that the state of resilience in rural areas is poorly evaluated. This assessment also shows that all villages have the same conditions in terms of economic and social resilience. Also, the result showed that three main or macro factors are effective in the resilience of rural areas and their improvement. These three factors are the prosperity of economic platforms and job creation, the promotion of human and social capital, as well as the creation of facilities and income capacities. Therefore, planning should be in line with emphasizing and promoting these factors by identifying influential indicators in this field. ReferencesPersian References- Dadashpour, H., & Adeli, Z. (2014). Measuring resilience capacities in Qazvin urban complex. Journal of Crisis Management, 4(8), 73-84.- Haddad, M., & Sadeghi, H. (2020). Analysis of the relationship between demographic factors and employment situation in the agricultural sector (Case study: Villages of Isfahan province. Quarterly Journal of Village and Space Sustainable Development, 1(3), 83-94.- Iran Statistics Center (2015). Population and housing census 2015. Tehran.- Keikha, Z., Bazrafshan, J., Ghanbari, S., & Keikha, A. (2020). Analysis of resilience of Sistan rural communities against environmental hazards. Journal of Natural Environment Hazards, 9(23), 1-18.- Khayam Bashi, E. (2011). Earthquake centered neighborhood crisis management. Second National Civil Engineering Conference, Islamic Azad University, Khomeinishahr Branch, Khomeinishahr.- Khosravi Mal Amiri, H., Soleimani, H., Ghaffari, S. R., & Khadem al-Hosseini, A. (2020). Explaining of resilience pattern of rural settlements in Izeh County (Dehdez district). Journal of Physical Social Planning, 7(1), 131-145.- Mododi Arkhodi, M., Boroumand, R., & Akbari, E. (2020). Explaining the resilience of rural areas against natural hazards with an emphasis on the flood. Journal of Natural Environment Hazards, 9(23), 151-172.- Pourahmad, A., Ziari, K., Abdali, Y., & Aleh Qolipour, S. (2018). Analysis of resiliency criteria in urban worn out texture of Tehran 10 municipality against earthquake with emphasis on physical resilience. Journal of Research and Urban Planning, 19(36), 1-21.- Safaei, A., Shariat Panahi, M., Bahak, B., Ranjbar, M., & Azadbakht, B. (2022). Analysis of resilience of rural areas against natural hazards (Case study: Golpayegan County). Quarterly Journal of Village and Space Sustainable Development, 3(4), 99-155.- Salimi, M., Naderi, A., & Nosrati, R. (2021). The study of rural community resilience against earthquakes (Case study: Kuaick rural complex, in Sarpol-e Zahab). Quarterly Journal of Social Studies and Research in Iran, 10(3), 831-886.- Sasanpour, F., Ahangari, N., & Hajinejad, S. (2017). Evaluating the urban resilience against natural hazards in 12 regions of Tehran Metropolis. Journal of Spatial Analysis of Environmental Hazards, 4(3), 85-98.- Shokri Firouzjah, P. (2017). Spatial analysis of the resilience of Babol's regions to environmental hazards. Journal of Physical Social Planning, 4(2), 27-44.- Taleshi, M., Ali Akbari, E., Jafari, M., & Seyed Akhlaghi, J. (2016). Developing and validating appropriate indices for rural resilience to drought (Case study: Hableroud Watershed Basine). Journal of Iran Pasture and Desert Research, 24(4), 881-896.- Zarghami, S., Teymouri, A., Mohammadian, H., & Shamaei, A. (2015). Measuring and evaluating urban neighborhood's resilience against earthquake: The case of Zanjan downtown. Journal of Research and Urban Planning, 7(27), 77-92.English References- Atara, A., Tolossa, D., & Denu, B. (2020). Analysis of rural households’ resilience to food insecurity: Does livelihood systems/choice/matter? The case of Boricha woreda of the sidama zone in southern Ethiopia. Journal of Environmental Development, 35(3), 43-59.- Buckle, P., Mars, G., & Smale, S. (2000). New approaches to assessing vulnerability and resilience. Australian Journal of Emergency Management, 15(2), 8-14.- Chen, W., & Zhang, L. (2021). Resilience assessment of regional areas against earthquakes using multi-source information fusion. Journal of Reliability Engineering & System Safety, 215(2), 215-233.- Drennan, L., & Morrissey, L. (2019). Resilience policy in practice surveying the role of community based organizations in local disaster management. Journal of Local Government Studies, 45(3), 328-349.- Fan, J., Mo, Y., Cai, Y., Zhao, Y., & Su, D. (2021). Evaluation of community resilience in rural China taking Licheng Subdistrict, Guangzhou as an example. International Journal of Environmental Research and Public Health, 18(11), 15-31.- Fekete, A. (2019). Critical infrastructure and flood resilience: Cascading effects beyond water. Wiley Interdisciplinary Reviews: Water, 6(5), 32-49.- Gunderson, L. H., Allen, C. R., & Holling, C. S. (Eds.) (2010). Foundations of ecological resilience. Washington: Island Press.- Hizbaron, D. R., Baiquni, M., Sartohadi, J., & Rijanta, R. (2012). Urban vulnerability in Bantul district, Indonesia towards safer and sustainable development. Sustainability, 4(9), 2022-2037.- Holling, C. S. (2007). Resilience and stability of ecological systems. Annual Review of Ecology and Systematics, 4(1), 1-23.- Jain, G. (2015). The role of private sector for reducing disaster risk in large scale infrastructure and real estate development: Case of Delhi. International Journal of Disaster Risk Reduction, 14(3), 238-255.- Keshavarz, M., & Moqadas, R. S. (2021). Assessing rural households' resilience and adaptation strategies to climate variability and change. Journal of Arid Environments, 184(2), 29-47.- Li, Y. (2023). A systematic review of rural resilience. China Agricultural Economic Review, 15(1), 66-77.- Mayunga, J. S. (2017). Understanding and applying the concept of community disaster resilience: A capital-based approach. Summer Academy for Social Vulnerability and Resilience Building, 1(1), 1-16.- Nikpour, A., & Yarahmadi, M. (2021). Identifying and explaining the drivers of physical resilience (Case study: Noorabad Mamasani). Journal of Physical Social Planning, 8(1), 85-98.- Pashapour, H., & Pourakrami, M. (2018). Measuring physical dimensions of urban resilience in the face of the natural disasters (Earthquake) (Case study: Tehran's 12th District). Journal of Studies of Human Settlements Planning, 12(4), 985-1002.- Sina, D., Chang-Richards, A. Y., Wilkinson, S., & Potangaroa, R. (2019). What does the future hold for relocated communities post-disaster? Factors affecting livelihood resilience. International Journal of Disaster Risk Reduction, 34, 173-183.- Tebboth, M. G. L., Conway, D., & Adger, W. N. (2019). Mobility endowment and entitlements mediate resilience in rural livelihood systems. Journal of Global Environmental Change, 54(2), 172-183.- Tromeur, E., M´enard, R., Bailly, J. B., & Souli´e, C. (2012). Urban vulnerability and resilience within the context of climate change. Journal of Natural Hazards and Earth System Sciences, 12(5), 1811–1821.- Zhou, W., Guo, S., Deng, X., & Xu, D. (2021). Livelihood resilience and strategies of rural residents of earthquake-threatened areas in Sichuan Province, China. Natural Hazards, 106(4), 255-275.